Pengaruh social media marketing, akreditasi, dan fasilitas terhadap intensi memilih Fakultas Ekonomi dan Bisnis Universitas Tarumanagara - Harun, Priadi; Widjaja, Indra (Jurnal Manajemen Bisnis dan Kewirausahaan, 2025)
The purpose of this study was to determine the impact of advertising on social media, accreditation and facilities on students' intentions in choosing the Faculty of Economics and Business, Tarumanagara University. This study uses a quantitative approach. The survey method is used to obtain or collect research data. The survey method is a research approach that involves collecting data from respondents or participants through questions or statements that have been prepared in advance. The sample will be taken using the non-probability sampling method because each member of the population has a different chance of being selected. This study uses a Likert scale, which usually consists of five responses. The data obtained from the results of the questionnaire distribution will be further analyzed using the SPSS (Statistical Program for Social Science) analysis tool to test validity and reliability. The results of the study have shown that there is a significant influence of Social Media Marketing, accreditation and facilities on the Intention to choose the Faculty of Economics and Business, Tarumanagara University. The results of the validity test on the four variables of Social Media Marketing, Facilities, Accreditation and Intention to choose the Faculty of Economics and Business, Tarumanagara University show that all are valid, because the calculated t value is greater than the t table value, so all statements are valid. In the Reliability test, it can be seen that all Cronbach's alpha values ​​are greater than 0.6 so that it can be said that all variables are reliable. Tujuan dari penelitian ini adalah untuk mengetahui dampak iklan di media sosial, akreditasi dan fasilitas terhadap intensi mahasiswa dalam memilih Fakultas Ekonomi dan Bisnis Universitas Tarumanagara. Penelitian ini menggunakan pendekatan kuantitatif. Metode survei digunakan untuk mendapatkan atau mengumpulkan data penelitian. Metode survei merupakan pendekatan penelitian yang melibatkan pengumpulan data dari responden atau partisipan melalui pertanyaan atau pernyataan yang telah dipersiapkan sebelumnya. Sampel akan diambil menggunakan metode non-probability sampling karena setiap anggota populasi memiliki peluang yang berbeda untuk dipilih. Penelitian ini menggunakan skala Likert, yang biasanya terdiri dari lima tanggapan. Data yang telah didapatkan dari hasil penyebaran kuesioner akan dilakukan analisis lebih lanjut menggunakan alat analisis SPSS (Statistical Program for Social Science) untuk dilakukan pengujian validitas dan reliabilitas. Hasil penelitian telah menunjukkan terdapat pengaruh yang signifikan dari Sosial Media Marketing, akreditasi dan fasilitas terhadap Intensi memilih Fakultas Ekonomi dan Bisnis Universitas Tarumanagara.